Development of Android-Based Learning Media Assisted by Appypie Pythagorean Theorem Material - Nurhayati, Siti; Hakim, Dori Lukman (Advances In Social Humanities Research, 2024)
Along with the influence of smartphones in terms of information and communication in every daily activity for both students and teachers, this causes the concentration and learning time of students to decrease. Based on the needs analysis interview results, information was obtained that students liked the material presented in the form of an Android application. This study aims to determine the feasibility of developing an Android-based learning media assisted by Appypie for the Pythagorean theorem material and student responses. The research method for developing Android-based learning media uses the R&D (Research and Development) development method. The development model used in this study refers to the 4-D development model from Thiagarajan, which consists of (1) Define, (2) Design, (3) Develop, and Disseminate. Data collection techniques in this study were interviews and questionnaires. Research instrument validation sheet of experts and students. The results of the research on the development of Android-based learning media assisted by Appypie are "very feasible" for media experts, with an average percentage of 80.77% and an average percentage of material experts of 94.44%. Student responses obtained an average percentage of 77.40% for small-scale trials and 76.80% for large-scale trials with the criteria of "very feasible"